Implementation of the Peer Tutor Model as an Effort to Increase the Effectiveness of Reading and Writing the Qur'an - Titih Rohilah (Global Writing Academica Researching & Publishing, 2022)
This study's objective was to assess the application of the peer tutor model in an effort to improve the capacity to read and write the Qur'an. This study employs a qualitative case study methodology. This research utilizes both primary and secondary data types. Observations and interviews with research respondents provided preliminary data for this study, which was done at State Senior High School 1 Cilaku, Cianjur district using the peer tutor approach. The Qur'an Reading and Writing Program with a peer tutor model implemented at the State Senior High School 1 Cilaku, Cianjur, was considered successful because it showed a significant change in students' ability to read the Qur'an. Those who initially were not fluent in reading the Qur'an, slowly but surely, their ability to read and write the Qur'an increased. This can be seen from their attendance list (who often attend Qur'an Reading and Writing, progress is also fast) compared to before participating in the Qur'an Reading and Writing program or those who rarely attend Qur'an Reading and Writing (because of permission or illness).